REKAYASA PERANGKAT LUNAK CROWFUNDING BASIRU MENGGUNAKAN PEMROGRAMAN PHP DAN FREAMWORK CODEIGNITER: REKAYASA PERANGKAT LUNAK CROWFUNDING BASIRU MENGGUNAKAN PEMROGRAMAN PHP DAN FREAMWORK CODEIGNITER - Sulas Tari; Farida Idifitriani; Nora Dery Sofya (Program Studi Informatika Universitas Teknologi Sumbawa, 2022)
The basiru tradition is a reflection of the collective life of the Sumbawa people, which holds the principle of mutual help. One of the activities that reflect the principle of gotong royong is the collection or crowdfunding of funds from the community to support certain activities that are donations/charities. Crowdfunding is a method of raising funds. Crowdfunding referred to in this study is a form of funding that uses a website-based application as a fundraising intermediary. While the crowdfunding model that will be used is Donation Based Crowdfunding. The data collection method used in this research is using qualitative methods and in its design using the Unified Modeling Language (UML) and the development method used is the Spiral method as a software development method. Basiru Crowfunding System Development Using PHP and Codeigniter Freamwork was built using the PHP programming language, Visual Studio Code and MySQL database as a Database Management System (DBMS) so that it is more efficient. The software testing method used is the black box software testing method, namely testing the device in terms of functionality.